Penyuluhan Manfaat Tanaman Obat Tradisional dan Pengelolaan Website Paguyuban Jamu Manunggal Kota Cimahi - Faramayuda, Fahrauk; Ilyas, Ridwan; Paramita, Veronika Santi; Windyaswari, Ari Sri; Ismail, Nursafira Khairunnisa; Akbar, Tzazkia Febriyana; Putri, Dhiffa Namira Alifia; Adriana, Reyhan (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Paguyuban Jamu Manunggal Cimahi is located at Gang M. Ardjo No.224. Based on the initial survey, the problem was identified that knowledge about the benefits of traditional medicinal plants was still limited. In addition, the sales of products are still ineffective because the marketing is still carried out conventionally. This underlies the need for counseling on the benefits of traditional medicinal plants and website management at Paguyuban Jamu Manunggal which aims to increase the knowledge of the participants and to expand the target market. The counseling activity was carried out on October 08, 2023 which began with a pre-test, presentation, post-test, and workshop. Based on the test results, it can be concluded that the counseling activities can significantly increase the knowledge of the participants, this is indicated by the average value of the pre-test and post-test which was originally 60 to 95.3.